The Influence of Competence on Employee Performance: Investigation of Automotive Companie - Herwina, Yulia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this research is to find out The Effect of Competence on Employee Performance.This research was conducted at an automotive company in Riau Indonesia. The sample is because the population is small, the entire population is used as a sample.Based on the data obtained, the following conclusions can be drawn:The result of simple linear regression is obtainedY=10,940+0.617X, it can be concluded that it has a positive direction of relationship. The results of the t_test show that competence has a significant effect on employee performance. The result of the coefficient of determination is 0.496. This means 49.6%employee performance variable is influenced or explained by the competency variable, while the remaining 50.4% is influenced by other variables not examined in this study.